Pengaruh Laporan Keuangan dan Pengelola Zakat Terhadap Kepercayaan Muzakki Pada Baitul Maal Hidayatullah Bengkulu - Hendri Hendri; Yuli Yusnita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze the influence of variables, namely the Influence of Financial Report Transparency and Zakat Management on Muzakki's Trust in Baitul Maal Hidayatullah (BMH) Bengkulu Representatives. As a non-profit organization, the Amil Zakat Institution needs to pay attention to the transparency of financial reports and zakat management regarding muzakki trust. In this research, data was collected through questionnaires distributed at the Bengkulu Representative Baitul Maal Hidayatullah (BMH) institution. The respondents in this study were muzakki BMH. The number of samples whose data were successfully processed was 84 muzakki. The sample selection method used is a non-probability method, namely convenience sampling, which is a sampling technique based on ease of access to members of the population. The results of hypothesis testing show that there is a positive influence of transparency of financial reports and zakat management on muzakki trust. This means that the higher the transparency of the institution's financial reports and zakat management, the higher the muzakki's trust in Baitul Maal Hidayatullah (BMH) Bengkulu Representative.